Easily-collapsible and easily-regenerated precoated sand and preparation method thereof
By replacing traditional raw sand with steel balls and combining specific resins and solutions, cast aluminum coated sand that is easy to collapse and regenerate is prepared, which solves the problems of high production costs and low yield in the existing technology, and achieves cost reduction and quality improvement.
Patent Information
- Application Number
- CN202411694388.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The production cost of existing cast aluminum coated sand is high and the preparation process requirements are strict, resulting in low yield and expensive cost.
Steel pills are used to replace traditional quartz sand or orb sand as the original sand, and coated sand that is easy to crumble and regenerate is prepared by combining phenolic resin, urottropine aqueous solution and calcium stearate.
The yield rate of cast aluminum coated sand is improved, production cost is reduced, and due to the excellent thermal conductivity and fluidity of steel balls, preparation time and energy consumption are reduced.
Smart Images

Figure BDA0005151765020000071 
Figure BDA0005151765020000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coated sand preparation, and in particular to easily disintegrated and easily regenerated coated sand and a preparation method thereof. Background Art
[0002] Aluminum coated sand is a sand material widely used in aluminum alloy casting, mainly used to improve the surface quality and precision of castings. It consists of base sand (usually quartz sand or bauxite sand) and a film layer covering its surface. The film layer is usually made of organic or inorganic coatings to enhance the strength, high temperature resistance and surface smoothness of the sand mold. Coated sand has good fire resistance and thermal stability, and can effectively withstand the high temperature pouring of molten aluminum.
[0003] However, aluminum casting coated sand also has some technical disadvantages. First, due to its complex manufacturing process and the expensive coating materials used, its cost is high, which makes coated sand less economical than traditional sand molds in some mass production. Secondly, the preparation process of coated sand is demanding, and the sand particle distribution and coating thickness need to be strictly controlled to ensure the quality of the casting. If it is not handled properly, it may lead to insufficient strength of the sand mold or uneven coating, which will affect the precision and surface quality of the casting. Summary of the invention
[0004] In order to overcome the problems of high production cost and high requirements for preparation process of cast aluminum coated sand commonly found in the prior art, the present invention provides a coated sand that is easy to disintegrate and regenerate, which comprises the following components by weight: 1000 parts of steel shot, 7-10 parts of phenolic resin, 2.9-4.5 parts of urotropine aqueous solution, and 4.9-7.5 parts of calcium stearate.
[0005] Preferably, the steel shot is made of stainless steel, the diameter of the steel shot is 40-200 meshes and the three-sieve concentration is greater than 85%.
[0006] Preferably, the urotropine aqueous solution is prepared from urotropine and water in a mass ratio of 1:2-1:3.
[0007] In addition, the present invention also provides a method for preparing easily disintegrated and easily regenerated coated sand, comprising: heating steel shots, and then sequentially adding phenolic resin, urotropine aqueous solution and calcium stearate to the steel shots in a stirring environment to obtain cast aluminum coated sand.
[0008] Preferably, when the steel shot is used aluminum casting waste sand, the aluminum casting waste sand needs to be regenerated.
[0009] Preferably, the regeneration process is to burn the waste aluminum casting sand at 450-500° C. for 1.8-2.5 hours.
[0010] Preferably, the steel shot is heated to 120-130°C.
[0011] Preferably, the heated steel shot is poured into a sand mixer, phenolic resin is added and stirred for 35-40 seconds, then the urotropine aqueous solution is added and stirred for 35-45 seconds, and finally calcium stearate is added and stirred for 20-25 seconds.
[0012] Beneficial effects:
[0013] The beneficial effects produced by the technical solution of the present invention are as follows:
[0014] The present invention adopts steel shot to replace commonly used quartz sand, gem sand and the like as raw sand to produce cast aluminum coated sand. Compared with commonly used quartz sand, gem sand and the like, the steel shot is closer to a sphere in shape and has an angular coefficient closer to 1. Therefore, the steel shot can be better and more evenly wrapped by the resin in the process of producing the coated sand, thereby improving the yield rate of the cast aluminum coated sand preparation. Since the steel shot has excellent thermal conductivity and fluidity, the heating time during preparation, the core making and shooting pressure, and the energy can be reduced, while the prepared cast aluminum coated sand can also have excellent disintegration properties. In addition, the steel shot is inexpensive, easy to regenerate, and can be reused, thereby greatly reducing the production cost of the cast aluminum coated sand. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Therefore, the following detailed description of the embodiments of the present invention provided is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0016] This embodiment adopts steel shot with an angular coefficient close to 1, good fluidity, thermal conductivity and low cost as raw sand to prepare cast aluminum coated sand, thereby solving the problems of high production cost and uneven distribution of resin coating in the prior art. The specific embodiments are as follows:
[0017] The invention discloses an easily disintegrated and easily regenerated coated sand, which comprises the following components by weight: 1000 parts of steel shot, 7-10 parts of phenolic resin, 2.9-4.5 parts of urotropine aqueous solution and 4.9-7.5 parts of calcium stearate.
[0018] Specifically, the steel shot is made of stainless steel, the diameter of the steel shot is 40-200 meshes and the three-sieve concentration is greater than 85%.
[0019] Specifically, the urotropine aqueous solution is prepared from urotropine and water in a mass ratio of 1:2-1:3.
[0020] A method for preparing easily disintegrated and easily regenerated coated sand comprises: heating steel shots, and then sequentially adding phenolic resin, urotropine aqueous solution and calcium stearate to the steel shots in a stirring environment to obtain cast aluminum coated sand.
[0021] Specifically, when the steel shot is used aluminum casting waste sand, the aluminum casting waste sand needs to be regenerated.
[0022] Specifically, the regeneration process is to burn the waste aluminum sand at 450-500°C for 1.8-2.5h.
[0023] Specifically, the steel shot is heated to 120-130°C.
[0024] Specifically, the heated steel shot is poured into a sand mixer, phenolic resin is added and stirred for 35-40 seconds, then the urotropine aqueous solution is added and stirred for 35-45 seconds, and finally calcium stearate is added and stirred for 20-25 seconds.
[0025] The present invention will be further described below through specific examples and comparative examples:
[0026] Example 1
[0027] In this embodiment, the coated sand includes the following components by weight: 1000 parts of steel shot, 7 parts of phenolic resin, 2.9 parts of urotropine aqueous solution, and 4.9 parts of calcium stearate.
[0028] The steel shot is made from recycled aluminum casting waste sand, the diameter of the steel shot is 40 / 70 mesh and the three-sieve concentration is 90%; the hexamine aqueous solution is prepared by mixing hexamine and water in a mass ratio of 1:2.
[0029] The preparation process of coated sand in this embodiment includes:
[0030] The cast aluminum waste sand was sintered at 450°C for 1.8 hours to obtain regenerated steel shots, and then the temperature of the steel shots was controlled at 120°C, poured into a sand mixer, and phenolic resin was added and stirred for 35 seconds, and then a urotropine aqueous solution was added and stirred for 35 seconds, and finally calcium stearate was added and stirred for 20 seconds to obtain coated sand.
[0031] Example 2
[0032] In this embodiment, the coated sand includes the following components by weight: 1000 parts of steel shot, 9 parts of phenolic resin, 3.8 parts of urotropine aqueous solution, and 6 parts of calcium stearate.
[0033] The steel shot is made from recycled aluminum casting waste sand, the diameter of the steel shot is 70 / 140 mesh and the three-sieve concentration is 95%; the hexamine aqueous solution is prepared from hexamine and water in a mass ratio of 1:3.
[0034] The preparation process of coated sand in this embodiment includes:
[0035] The cast aluminum waste sand was sintered at 475°C for 2 hours to obtain regenerated steel shots, and then the temperature of the steel shots was controlled at 125°C, poured into a sand mixer, and phenolic resin was added and stirred for 37 seconds, followed by adding urotropine aqueous solution and stirring for 40 seconds, and finally adding calcium stearate and stirring for 23 seconds to obtain coated sand.
[0036] Example 3
[0037] In this embodiment, the coated sand includes the following components by weight: 1000 parts of steel shot, 10 parts of phenolic resin, 4.5 parts of urotropine aqueous solution, and 7.5 parts of calcium stearate.
[0038] The steel shot is made from recycled aluminum casting waste sand, the diameter of the steel shot is 200 meshes and the three-sieve concentration is 95%; the hexamine aqueous solution is prepared by mixing hexamine and water in a mass ratio of 1:3.
[0039] The preparation process of coated sand in this embodiment includes:
[0040] The cast aluminum waste sand was sintered at 500°C for 2.5 hours to obtain regenerated steel shots, the temperature of the steel shots was controlled at 130°C, then poured into a sand mixer and added with phenolic resin and stirred for 40 seconds, then added with urotropine aqueous solution and stirred for 45 seconds, and finally added with calcium stearate and stirred for 25 seconds to obtain coated sand.
[0041] Example 4
[0042] In this embodiment, the coated sand includes the following components by weight: 1000 parts of steel shot, 9 parts of phenolic resin, 3.8 parts of urotropine aqueous solution, and 6 parts of calcium stearate.
[0043] The diameter of the steel shot is 70 / 140 mesh and the three-sieve concentration is 95%; the urotropine aqueous solution is prepared by mixing urotropine and water in a mass ratio of 1:3.
[0044] The preparation process of coated sand in this embodiment includes:
[0045] The steel shot was heated to 125°C, then poured into a sand mixer and phenolic resin was added and stirred for 37 seconds, then the urotropine aqueous solution was added and stirred for 40 seconds, and finally calcium stearate was added and stirred for 23 seconds to obtain coated sand.
[0046] Comparative Example 1
[0047] In this comparative example, quartz sand was used as raw sand.
[0048] The remaining components and contents of the coated sand in this comparative example are the same as those in Example 4.
[0049] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0050] Comparative Example 2
[0051] The components and contents of the coated sand in this comparative example are the same as those in Example 4.
[0052] The diameter of the steel shot in this comparative example is 20 / 40 mesh.
[0053] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0054] Comparative Example 3
[0055] The components and contents of the coated sand in this comparative example are the same as those in Example 4.
[0056] The diameter of the steel shot in this comparative example is 200 / 300 mesh.
[0057] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0058] Comparative Example 4
[0059] The components and contents of the coated sand in this comparative example are the same as those in Example 4.
[0060] The three-sieve concentration of the steel shot in this comparative example is 83%.
[0061] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0062] Comparative Example 5
[0063] In this comparative example, the coated sand includes the following components by weight: 1000 parts of steel shot, 6.8 parts of phenolic resin, 3.8 parts of urotropine aqueous solution, and 6 parts of calcium stearate.
[0064] The specifications of the steel shot and the ratio of the urotropine aqueous solution in this comparative example are the same as those in Example 4.
[0065] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0066] Comparative Example 6
[0067] In this comparative example, the coated sand includes the following components by weight: 1000 parts of steel shot, 10.3 parts of phenolic resin, 3.8 parts of urotropine aqueous solution, and 6 parts of calcium stearate.
[0068] The specifications of the steel shot and the ratio of the urotropine aqueous solution in this comparative example are the same as those in Example 4.
[0069] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0070] Comparative Example 7
[0071] In this comparative example, the coated sand includes the following components by weight: 1000 parts of steel shot, 9 parts of phenolic resin, 2.6 parts of urotropine aqueous solution, and 4.5 parts of calcium stearate.
[0072] The specifications of the steel shot and the ratio of the urotropine aqueous solution in this comparative example are the same as those in Example 4.
[0073] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0074] Comparative Example 8
[0075] In this comparative example, the coated sand includes the following components by weight: 1000 parts of steel shot, 9 parts of phenolic resin, 4.7 parts of urotropine aqueous solution, and 7.8 parts of calcium stearate.
[0076] The specifications of the steel shot and the ratio of the urotropine aqueous solution in this comparative example are the same as those in Example 4.
[0077] The preparation process of the coated sand in this comparative example is the same as that in Example 4.
[0078] The coated sand prepared in this embodiment and the comparative example was tested for its high temperature resistance, gas evolution, fluidity and other properties according to the national standard JB / T8583-2008 "Coated Sand for Casting". The detailed test results are shown in Table 1.
[0079] Table 1 Coated sand performance test results
[0080]
[0081]
[0082] From the test results of the above embodiments and comparative examples in Table 1, we can see that the cast aluminum coated sand prepared within the range given by the present invention has good disintegration, gas emission and fluidity, and can achieve easy regeneration and disintegration of the cast aluminum coated sand. At the same time, the yield rate of coated sand casting is greatly improved; and from the test results of Example 4 and Comparative Example 1, we can see that compared with traditional quartz sand, the coated sand prepared by using steel shots has a higher yield rate and has lower gas emission and better fluidity and disintegration, which can enable the coated sand to improve casting accuracy and avoid defects such as sand holes and pores. At the same time, the coated sand can be better broken during demolding, thereby improving the casting speed and casting quality.
[0083] From the test results of Example 4 and Comparative Examples 2-3, we can see that the diameter of the steel shot and the three-screen concentration have a great influence on the final product of the coated sand. If the diameter of the steel shot is too small, the strength and gas emission of the prepared coated sand will be reduced, thereby reducing the collapsibility of the coated sand; and if the diameter of the steel shot is too large, the yield rate of the prepared coated sand will be extremely low, making the prepared coated sand almost unusable; the three-screen concentration of the steel shot is less than 85%, and the various properties of the steel shot prepared with a three-screen concentration greater than 85% are reduced. Finally, from the test results of Example 4 and Comparative Examples 5-8, we can see that a small amount or an excess of the remaining components in the coated sand will make the final coated sand worse in terms of collapsibility, strength, fluidity and yield rate compared to the coated sand prepared within the range given in the present invention.
[0084] The coated sand prepared by the present invention using steel shot with a diameter of 40-200 meshes and a three-sieve concentration of 85% as raw sand has the advantages of excellent disintegration and fluidity, and can meet the performance requirements of cast aluminum coated sand. In addition, the resin coating can be more evenly distributed on the surface of the steel shot by using the characteristics that the angular coefficient of the steel shot is approximately equal to 1 and is closer to a sphere than the commonly used raw sand, thereby improving the yield rate of cast aluminum coated sand. Combined with the characteristics that the coated sand prepared by the steel shot is easy to regenerate, the preparation cost of cast aluminum coated sand can be greatly reduced.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A kind of easily disintegrated and regenerated coated sand, characterized in that: The invention comprises the following components by weight: 1000 parts of steel shot, 7-10 parts of phenolic resin, 2.9-4.5 parts of urotropine aqueous solution and 4.9-7.5 parts of calcium stearate.
2. The easily disintegratable and easily regenerated coated sand according to claim 1, characterized in that: The steel shot is made of stainless steel, the diameter of the steel shot is 40-200 mesh and the three-sieve concentration is > 85% 。 3. The easily disintegratable and easily regenerated coated sand according to claim 1, characterized in that: The hexamethylenetetramine aqueous solution is prepared from hexamethylenetetramine and water in a mass ratio of 1:2-1:
3.
4. A method for preparing easily disintegratable and easily regenerated coated sand according to any one of claims 1 to 3, characterized in that: include: The steel shot is heated, and then phenolic resin, urotropine aqueous solution and calcium stearate are sequentially added to the steel shot in a stirring environment to obtain cast aluminum coated sand.
5. The method for preparing the easily disintegrable and easily regenerated coated sand according to claim 4, characterized in that: When the steel shot is used aluminum casting waste sand, the aluminum casting waste sand needs to be regenerated.
6. The method for preparing the easily disintegrable and easily regenerated coated sand according to claim 5, characterized in that: The regeneration process is to burn the aluminum casting waste sand at 450-500° C. for 1.8-2.5 hours.
7. The method for preparing the easily disintegrable and easily regenerated coated sand according to claim 4, characterized in that: The steel shot is heated to 120-130°C.
8. The method for preparing the easily disintegrable and easily regenerated coated sand according to claim 4, characterized in that: Pour the heated steel shot into a sand mixer, add phenolic resin and stir for 35-40 seconds, then add urotropine aqueous solution and stir for 35-45 seconds, and finally add calcium stearate and stir for 20-25 seconds.
Citation Information
Cited By
Anti-caking precoated sand and preparation method thereof
CN122352818A